Exploring Farmers' Resilience: Climate Change and Sustainable Adaptation Strategies in the Agricultural Sector of Nepal - Shikha Sharma; Srijana Neupane (Turkish Journal of Agriculture: Food Science and Technology)
Agriculture is a cornerstone of the economy, providing livelihoods for a significant portion of population. However, climate change significantly affects people, their lifestyles, and the ecosystems posing a critical challenge to the global community, particularly the underprivileged in developing nations. Recognizing the indispensable role of agriculture and the challenges posed by a changing climate, this paper emphasizes the paramount need for proactive adaptation strategies. Central to these strategies is the pivotal concept of Climate-Smart Agriculture (CSA), a multifaceted approach that encompasses a range of practices, including agroforestry, conservation agriculture, and the adoption of climate-resilient crop varieties. Delving deeper, the paper navigates through the farmer's perceptions, unraveling their understanding of climate change, and the complex barriers like social barriers, institutional limitations, financial barriers, and limited awareness that impede effective adaptation, and illuminates the instrumental roles that governmental bodies and institutions, and extension agents play in shaping and fostering climate-resilient practices. Collaboration between local communities, governments, and non-governmental organizations is essential to ensure the successful implementation of sustainable adaptation strategies. Embracing sustainable and forward-thinking approaches, particularly CSA, including agroforestry, conservation agriculture, water management techniques, climate-resilient crop varieties, ICT, and climate-smart pest management, the agricultural sector gains the potential to bolster its resilience against climate-induced disruptions, ensuring consistent agricultural output that contributes significantly to broader food security initiatives.